Retinal detachment in retinitis pigmentosa. Issue 1 (9th July 2020) - Chan, Weng Onn; Brennan, Nicholas; Webster, Andrew R; Michealides, Michel; Muqit, Mahiul M K
Abstract : Objective: Retinitis pigmentosa-related retinal detachment (RPRD) is rare, and the full spectrum of retinal complications is not well defined. To describe the types of retinal detachment in patients with retinitis pigmentosa and the surgical outcomes of RPRD. Methods: This is a non-comparative, retrospective case series. An electronic database search was performed using Moorfields OpenEyes electronic health records. We identified 90 patients with RPRD between January 2000 and August 2017. Main outcome and measures are visual acuity (VA), surgical outcomes and classification of RPRD. Results: Of the 90 patients/detachments, 61 (67.8%) were rhegmatogenous retinal detachment (RRD), 19 (21.1%) were exudative, 3 (3.3%) were tractional retinal detachment (TRD) and 7 (7.8%) had combined. 37.5% (9/24) of patients with exudative retinal detachment were treated with either cryotherapy or laser, and one patient underwent vitrectomy for vitreous haemorrhage. 56/90 patients underwent surgical intervention. Nine patients presented late and were deemed inoperable (two exudative and seven RRD). Of the RRD patients with full operative record, the primary attachment rate was 76.2% (16/21) and final reattachment rate was 85.7% (18/21) over a mean 15.4-year follow-up period. Mean VA for RRD surgery improved from 6/190 (1.51 logMAR) to 6/120 (1.31 logMAR) (p=0.194). In the TRD group, the mean VA was 6/300 (1.66 logMAR) at baseline and improved after surgery to 6/48 (0.90 logMAR) (p=0.421). Conclusions: We demonstrated a final reattachment rate of 85.7% with a trend toward better vision following intervention for patients with RPRD. However, the final long-term vision may be poor due to the natural progression of retinitis pigmentosa-associated macular degeneration.